The Relationship of the use of Injected Hormonal Contraception with the Event of White about KB Accepters in The Working Area of the Singosari Inpatient Health Center, Pematang Siantar City, In 2022 - Masta Tambun (Science Midwifery, 2022)
A Family Planning (KB) is an effort to regulate the birth of children, distance, and the ideal age of childbirth, regulate pregnancy, through promotion, protection, and assistance in accordance with reproductive rights to realize a quality family This research was carried out in the work area of the inpatient health center Singosari Pematang Siantar in 2022 The reason for choosing this location is because the use of contraceptives in men in this region is still lacking. The type of research used in this study is observational analytics with a cross-sectional research design . The data collection technique used in this study was to provide a list of questions (questionnaires) to the research targets related to or related to the use of injectable-type contraceptives and the incidence of vaginal discharge in respondents. . The population in this study were acceptors of injectable birth control for 1 month and 3 months who experienced vaginal discharge in the Working Area of the Singosari Pematang Siantar Inpatient Health Center in 2022'. A total of 41 people. The sampling technique used in this study is purvosive sampling or the sample that is used as the object of research is what has been determined as a sample, namely respondents who experienced vaginal discharge because they used 1 month of injectable birth control and 3 months of injectable birth control, which was 41 people. Chi-Square test results state Ho is rejected if the probability of <0.05. The results of the chi-square test analysis were obtained df = 1, and nulai p value (p = 0.005<0.05) then Ho was rejected and Ha was accepted, then there was a significant relationship between the use of injectable hormonal birth control and the incidence of vaginal discharge in the acceptor of birth control in the work area of the Singosari Pematang Siantar Inpatient Health Center in 2022. It is hoped that midwives will further improve counseling regarding the use and side effects of hormonal contraceptives, and encourage acceptors to maintain the cleanliness of reproductive devices so as to avoid the occurrence of vaginal discharge.